2021
DOI: 10.1186/s12995-021-00318-y
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and work-life balance among physicians: the role of migration background

Abstract: Background We want to analyze the effect of migration background (MB) on physician burnout and work-life balance. Methods In September 2019, physicians from various specialties answered a questionnaire on work and health. We analyzed a subsample of 526 physicians that were working full time in a hospital, 14% with an MB and 47.9% were female. Results Multivariate analysis showed that physicians with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In the current study, 37.2% mentioned child care as a reason for work hour reduction. In addition, age has been related to lower levels of psychological distress and burnout in physicians [ 43 , 44 ]. So far, evidence regarding different levels of burnout exhibited by different medical specialties or between physicians working in hospitals or ambulatory settings is rather mixed.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, 37.2% mentioned child care as a reason for work hour reduction. In addition, age has been related to lower levels of psychological distress and burnout in physicians [ 43 , 44 ]. So far, evidence regarding different levels of burnout exhibited by different medical specialties or between physicians working in hospitals or ambulatory settings is rather mixed.…”
Section: Discussionmentioning
confidence: 99%
“…60,63 This study also showed that non-Kuwaiti participants had high levels of personal burnout, which is consistent with the evidence in the literature that non-nationals are more prone to professional burnout. 66 This can be related to the fact that non-national physicians are not receiving professional support and have less work-related well-being than national physicians. 67 This study also showed that participants who worked in 3 GGHs during the Covid-19 pandemic had high levels of work-related burnout, which is also consistent with the evidence on the effect of the pandemic on healthcare workers' professional burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians in the original sample came from a variety of different specialties including internal medicine, surgery, neurology, and prevention. The sample was already used to analyze burnout and WLB in specific groups of physicians, i.e., specialists in internal medicine and physicians with a migration background [ 20 , 21 ]. For our analysis, we utilized a subsample consisting of all GPs working full time.…”
Section: Methodsmentioning
confidence: 99%